Accounting for asymmetry between strengths, weaknesses, opportunities and threats in outranking methods - Nassim Dehouche (2018)
© 2017, © Emerald Publishing Limited. Purpose: The purpose of this paper consists in discussing and modeling the asymmetrical nature of evaluation criteria that are notably relevant in strategic planning, project portfolio management and complex systems management. Design/methodology/approach: The author guarantees the theoretic validity of the proposed approach, by showing that it possesses desirable properties such as monotonicity. This allows for a reduced implementation time and thus a real-time use of the model. Findings: The author conducts a comparative study with two other multicriteria decision aid models on a set of real data regarding a power plant sitting problem and highlights some of the limitations of previous models compared to the proposed approach. Originality/value: This paper describes a novel multicriteria decision aid model, entitled SPADE (which is an acronym for Structuring Preferences to Aid DEcisions). It aims at consolidating SWOT analysis with sound decision-theoretic techniques, and making use of its results to support decision-making.